Manajemen Pengelolaan Bank Sampah di Kota Bekasi - Elvira Suryani (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam '45 (UNISMA) Bekasi, 2016)
Increasing population , and an increase in consumption patterns of the various products imposes a buildup of waste from households . Garbage is usually dumped into landfills to be piled up. To overcome this problem the government implements policies and breakthrough